Residual strength of blast damaged reinforced concrete columns - Bao, Xiaoli (2012)
Columns are the key load-bearing elements in frame structures and exterior columns are probably the most vulnerable structural components to terrorist attacks. Column failure is normally the primary cause of progressive failure in frame structures. A high-fidelity physics-based computer program, LS-DYNA was utilized in this study to provide numerical simulations of the dynamic responses and residual axial strength of reinforced concrete columns subjected to short standoff blast conditions. The finite element (FE) model is discussed in detail and verified through correlated experimental studies. An extensive parametric study was carried out on a series of 12 columns to investigate the effects of transverse reinforcement ratio, axial load ratio, longitudinal reinforcement ratio, and column aspect ratio. These various parameters were incorporated into a proposed formula, capable of estimating the residual axial capacity ratio based on the mid-height displacement to height ratios.